ASSOCIATIONS BETWEEN HBA1C LEVELS AND LIVER FUNCTION TESTS IN DIABETES: A COMPREHENSIVE ANALYSIS - JOSEPH KI; SIVAGAMI K; MOHAN KUMAR; APARNAVI P; JEEVITHAN S (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To determine the liver function tests status among the diabetic patients. Diabetes mellitus (DM) is a chronic multi-system disease characterized by hyperglycemia. The most common type of DM, Type 2 DM (T2DM), is characterized by insulin resistance and insufficient insulin secretory response. T2DM is frequently associated with abnormal liver function tests (LFTs). Our study aims to widen our knowledge of the complex interrelationship between T2DM and LFTs. Methodology: This study was done in a multi-specialty hospital in Western part of Tamil Nadu among the patients who came for master health check-up between 2017 and 2024. From the laboratory database of 67,000 patients, patients who reported for the 1st time and had their hemoglobin A1c (HbA1c) and LFT values evaluated were selected. They were categorized as normal, pre-diabetic, and diabetic based on HbA1c values. Data were analyzed using SPSS 27. Categorical variables were expressed in the form of frequency and percentages whereas continuous variables were expressed in the form of mean and standard deviation. Analysis of variance (ANOVA) was used to find out any significant difference in lipid profile among the three groups. Results: Our study had 23,238 participants. Out of them 7168 (30.84%) had normal HbA1c levels, 8347 (35.91%) were pre-diabetics and 7955 (34.23%) were diabetic patients. The mean total protein (TP), serum glutamic-pyruvic transaminase (SGPT), and alkaline phosphatase (ALP) were higher among the diabetic patients. ANOVA showed that there was a significant difference in serum total bilirubin, TP, albumin, serum glutamic-oxaloacetic transaminase (SGOT), SGPT, and ALP between the three groups. Pearson correlation coefficient showed a positive correlation between SGOT, SGPT, ALP, and HbA1c. It showed a negative correlation between TB, albumin, and HbA1c. Conclusion: From the findings of this study, there is evidence that there exists a significant association between HbA1c levels and LFTs. Elevated HbA1c levels correlate with abnormal LFT results, suggesting a potential link between glycemic control and liver health. These results underscore the need for monitoring both HbA1c and LFTs in patients with diabetes to manage their overall health comprehensively.